Treatment of Psoriasis with the Help of Curcumin Hydrogel - Gupta, Yash; Kumar, Neeraj; Shukla, Amrita; Rai, Vishal (Journal for Research in Applied Sciences and Biotechnology, 2023)
Psoriasis is a chronic inflammatory skin disorder that affects millions of people worldwide. Current treatments for psoriasis include topical corticosteroids, immunomodulators, and phototherapy, but these treatments may have limited efficacy or cause side effects. Curcumin, a natural compound with anti-inflammatory and antioxidant properties, has been shown to have potential as an alternative treatment for psoriasis. However, the low solubility and bioavailability of curcumin limit its effectiveness when administered orally or topically. Curcumin hydrogel, a topical formulation of curcumin, has been developed to address these limitations. In this review, we summarize the current research on the use of curcumin hydrogel in the treatment of psoriasis. We discuss the pharmacological properties of curcumin, the formulation of curcumin hydrogel, and the preclinical and clinical studies investigating the efficacy and safety of curcumin hydrogel in psoriasis. Overall, the available evidence suggests that curcumin hydrogel may be a promising alternative treatment for psoriasis, with potential benefits in reducing inflammation, promoting wound healing, and improving overall quality of life for psoriasis patients. Further research is needed to fully elucidate the mechanism of action of curcumin hydrogel and to optimize its formulation and delivery for maximum efficacy.